2018
DOI: 10.3233/mnm-17158
|View full text |Cite
|
Sign up to set email alerts
|

Soft drink consumption: Do we know what we drink and its implication on health?

Abstract: BACKGROUND: Intake of sugar sweetened beverages has been consistently linked to increased risk of obesity, type 2 diabetes, osteoporosis and cardiovascular disease, among other diseases. Putative underlying mechanisms include incomplete compensation for liquid calories, adverse glycemic effects, and increased hepatic metabolism of fructose leading to de novo lipogenesis, production of uric acid, and accumulation of visceral and ectopic fat. OBJECTIVE: This study aims to elucidate any existing link between ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A greater presence of obesity, gastritis constipation and mental illness among people who consume cola soft drinks more. (Martín et al, 2018) A cross-sectional study was carried out on 6-12 years of school-going children. Data about the consumption of sugar-containing foods and dental history were obtained.…”
Section: Study Results Referencesmentioning
confidence: 99%
“…A greater presence of obesity, gastritis constipation and mental illness among people who consume cola soft drinks more. (Martín et al, 2018) A cross-sectional study was carried out on 6-12 years of school-going children. Data about the consumption of sugar-containing foods and dental history were obtained.…”
Section: Study Results Referencesmentioning
confidence: 99%
“…The respondents in the study identified the type of drinks, such as sugar-sweetened beverages, as the main culprit in causing obesity. Sugar-sweetened beverages are linked to obesity due to increased energy intake and frequent consumption, leading to weight gain [18]. In a study conducted among Mexican adults [19], it was observed that increased sugar-sweetened beverages were associated with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“… A greater presence of obesity, gastritis constipation and mental illness among people who consume cola soft drinks more. ( Martín et al., 2018 ) A cross-sectional study was carried out on 6–12 years of school-going children. Data about the consumption of sugar-containing foods and dental history were obtained.…”
Section: Excess Sugar – a Source Of Diseases And Disordersmentioning
confidence: 99%